EXTERNAL MUNICIPAL FINANCIAL CONTROL IN THE REPUBLIC OF TUVA: REALITIES AND PROSPECTS - V. K. Khomushku (Publishing House of the State University of Management, 2019)
The features and problems of the development of external municipal financial control have been considered. According to the results of the analysis of the activity of the ISSC, the main reasons and factors, affecting the effectiveness of their activities have been determined. It has been noted, that due to the lack of the possibility of forming CSR with a number, that allows you for the full and qualitative implementation of the powers vested in CSR, the external municipal financial control in the republic needs to be reformed. Based on the study, it has been concluded, that it is necessary to initiate the transfer of authority of the ISSA to the level of the subject through the implementation of a pilot project to transfer the authority of CSR, the municipality that is least covered by external financial control to the level of the Audit Chamber of the Republic of Tuva. In the case of the implementation of this project, the quality of fulfilling the powers to conduct examination of municipal legal acts, control and expert-analytical activities, and reduce control risks will increase.